Digitalisasi Layanan Administrasi Akademik: Evaluasi Pengalaman, Kendala, dan Kebutuhan Mahasiswa - Muhamad Januaripin; Widodo Winarso; Cecep Sumarna; Ubed Jubaedah (Universitas Negeri Malang, 2025)
Abstract: The digitalization of academic administrative services in higher education has become a significant trend, particularly since the COVID-19 pandemic accelerated technology-driven transformations in education. Institut Miftahul Huda Subang is among the institutions that have implemented a digital system to improve efficiency, transparency, and accessibility of academic services. This study aims to evaluate students’ perceptions of digital administrative services, focusing on user experience, expectations for development, technical challenges, and training needs. The research employs a descriptive quantitative method, with data collected through an online questionnaire distributed to 145 active students. Data analysis was conducted using descriptive statistics and interpreted within the framework of the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and the DeLone & McLean Information System Success Model. The findings indicate that most students perceive the campus digital system as beneficial, with an average user experience score of 3.82 on a 5-point scale. However, several technical issues remain, particularly related to system feature comprehension, access speed, and availability of support services. Students also expressed high expectations for system improvement, such as more responsive features, automated notifications, easier access, and better integration of academic services, reflected in an average expectation score of 4.07. Furthermore, the need for training and user assistance emerged as highly significant (mean 4.17), suggesting that the optimal use of digital systems relies heavily on adequate technical support and user guidance. These results emphasize the importance of a holistic approach to the digitalization of academic services, which should not only prioritize technological availability but also ensure service quality, technical support, and user readiness. The study contributes to strategies for developing user-oriented academic information systems and expands the discourse on digital transformation in non-instructional aspects of higher education in Indonesia. Keywords: Academic Digitization, Digital Administration System, Campus Services Abstrak: Digitalisasi layanan administrasi akademik di perguruan tinggi telah menjadi fenomena penting, terutama sejak pandemi COVID-19 mendorong percepatan transformasi pendidikan berbasis teknologi. Institut Miftahul Huda Subang merupakan salah satu institusi yang menerapkan sistem digital untuk meningkatkan efisiensi, transparansi, dan aksesibilitas layanan akademik. Penelitian ini bertujuan untuk mengevaluasi persepsi mahasiswa terhadap layanan administrasi digital dengan fokus pada pengalaman penggunaan, harapan pengembangan, kendala teknis, dan kebutuhan pelatihan. Metode penelitian yang digunakan adalah kuantitatif deskriptif dengan pengumpulan data melalui kuesioner daring dari 145 mahasiswa aktif. Analisis data menggunakan statistik deskriptif dan dikaitkan dengan kerangka teoritis Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), dan Model Keberhasilan Sistem Informasi DeLone & McLean. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa menilai sistem digital kampus cukup baik dan bermanfaat, dengan rata-rata skor pengalaman penggunaan 3,82 dari skala 5. Namun, terdapat kendala teknis yang masih dihadapi, terutama terkait pemahaman fitur sistem, kecepatan akses, dan ketersediaan layanan bantuan. Mahasiswa menunjukkan harapan tinggi terhadap pengembangan fitur yang lebih responsif, seperti notifikasi otomatis, akses yang lebih mudah, dan integrasi layanan akademik yang lebih efisien, dengan skor rata-rata harapan 4,07. Selain itu, kebutuhan pelatihan dan pendampingan pengguna tercatat signifikan (mean 4,17), menunjukkan bahwa kesiapan mahasiswa dalam memanfaatkan sistem digital optimal bergantung pada dukungan teknis dan bimbingan penggunaan. Temuan ini menegaskan pentingnya pendekatan holistik dalam digitalisasi layanan akademik, yang tidak hanya fokus pada ketersediaan teknologi, tetapi juga pada kualitas layanan, dukungan teknis, dan kesiapan pengguna. Penelitian ini memberikan kontribusi bagi strategi pengembangan sistem informasi akademik yang berorientasi pada pengalaman pengguna, serta memperluas kajian transformasi digital non-instruksional di perguruan tinggi Indonesia. Kata kunci: Digitalsiasi Akademik, Sistem Administrasi Digital, Layanan Kampus